Praktik Maladministrasi di Pemerintah Daerah: Respon Ombudsman dalam Kasus Pelayanan Publik: Respon Ombudsman dalam Kasus Pelayanan Publik - Pandu Pamungkas; Annisa Larasati Chairani (Jurnal Penelitian Ilmiah INTAJ, 2026)
Maladministration in the management of public services remains a significant challenge faced by local governments in Indonesia. Maladministrative practices not only reduce the quality of public services but also erode public trust in government institutions and weaken public sector integrity. This study aims to analyse the forms of maladministration in local government public services and to examine the role of the Ombudsman in conducting interventions and supervision to improve governance. This research employs a qualitative approach using a case study method, focusing on the handling of public complaints related to public services in a selected local government. Data were collected through document analysis and review of Ombudsman reports. The findings indicate that maladministration manifests in various forms, including undue delay, procedural deviation, failure to provide services, and abuse of authority. The Ombudsman plays a crucial role in improving public services through examination processes, recommendations, and compliance monitoring. However, the effectiveness of the Ombudsman’s role faces several challenges, particularly the low level of compliance by local governments with the issued recommendations.